Precarização, preconceitos e resistências na institucionalização da educação a distância em instituições públicas de ensino superior - Pareschi, Claudinei Zagui (Universidade Federal de São Carlos, 2026)
In recent years, Distance Education (DE) has expanded significantly in Brazilian higher education, especially after the creation of the Open University of Brazil System (UAB). Despite this expansion, its incorporation into the academic, administrative, and pedagogical structures of Public Higher Education Institutions (PHEIs) remains marked by tensions, disputes, and limitations that hinder its institutional consolidation. This thesis analyzes how prejudice and resistance, the precarization of teaching work, and perceptions of quality influence the process of institutionalizing DE in PHEIs, seeking to understand the factors that hinder or foster this movement. Grounded in historical-dialectical materialism, in dialogue with the Freirean framework, the study adopts a qualitative-descriptive approach and is developed through methodological triangulation, combining a systematic literature review, an online questionnaire with 245 valid responses, and 14 semi-structured interviews with faculty members from public institutions. The results indicate that prejudice against DE remains associated with the idea of lower academic quality and with the persistence of hierarchies between teaching modalities. They also indicate that resistance to the modality assumes different meanings: in part, it is sustained by prior judgments and by the defense of the superiority of face-to-face education; in part, it is constituted as a critique of the concrete conditions under which DE was implemented and maintained in public universities. The study also shows that the precarization of teaching work, expressed in the dependence on external funding, grant-based remuneration, the fragmentation of pedagogical functions, and insufficient institutional recognition, directly affects the place occupied by DE in PHEIs. With regard to quality, the data indicate that it depends on effective institutional conditions of provision, involving pedagogical design, infrastructure, technical-pedagogical support, faculty education, work organization, and academic recognition. The results of the study support the argument that the institutionalization of DE in public universities occurs in an uneven and unfinished manner, marked by contradictions that connect expansion, precarization, partial recognition, and the persistence of prejudice and resistance. It is concluded that its consolidation requires stable funding, the valorization of teaching work, the organic incorporation of the modality into the institutional project of universities, and the confrontation of the forms of disqualification that still affect DE.
Precarization, prejudice, and resistance in the institutionalization of distance education in public higher education institutions
Keywords: Institucionalização da Educação a Distância; Preconceito; Resistência; Precarização do trabalho docente; Qualidade na EaD; Institutionalization of Distance Education; Resistance; Precarization of teaching work; Quality in Distance Education; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade